Frasa Nominal Atributif dalam Bahasa Indonesia: Indonesian Attributive Nominal Phrase - Ghufar, Ahmad Maulana; Pramono, Sigit; Rizqin Nikmatullah, Miftahula (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This research aims to describe the functions, categories, and meaning relationships in attributive nominal phrases in short stories. A qualitative descriptive approach is used in this research. As mentioned earlier, the data source of this research is an Indonesian short story entitled Jasmine by Gol A Gong which reflects the complexity of social reality. The listening and note-taking techniques are used in the data collection stage to identify attributive nominal phrases. The data obtained were analyzed using agih method with bagi unsur langsung (BUL) technique and presented in tree diagram and description, so that the structure pattern and relationship between elements in the phrase can be revealed clearly. The results of this study show that attributive nominal phrases in Indonesian can be constructed by several categories, including: N+N, N+A, Num+N, Sd+N, yang+N, and yang+V.  There are also meaning relationships between elements in attributive nominal phrases, including: illuminator, delimiter, determiner or pointer, number, and designation. Meanwhile, in analyzing the function of sentences in the form of attributive nominal phrases, it is possible to reveal the message that the author tries to raise in his short story through the highlighted subject.